Sosialisasi Cyber Security Awareness: Mitigasi Phishing dan Pengamanan Akun Digital bagi Siswa SMA/SMK - Hendy Prasetyo; Kameliani Kameliani; Wildan Wildan; Andi Rasya; Argiyo Prasetyo Tutu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Ichsan Gorontalo, 2026)
The widespread internet access in Indonesia has positioned senior high school and vocational students as the most active digital users while simultaneously making them the most vulnerable group to phishing attacks and digital account hijacking. The gap between technical proficiency and digital security awareness among adolescents has become an urgent issue requiring structured intervention. This community service activity aimed to enhance the cyber security awareness of students at SMAN 1 Limboto, Gorontalo Regency, through socialization focusing on three main aspects: phishing identification and mitigation, digital account security through Two-Factor Authentication (2FA), and data privacy principles in daily online activities. The activity employed an interactive lecture method based on real-life case studies relevant to adolescents' digital lives, complemented by live demonstrations and question-and-answer sessions. Evaluation through an interactive quiz revealed an average increase of 58 percentage points across all comprehension indicators, from 33% before to 91% after the socialization, with the highest increase recorded on the 2FA knowledge indicator at 63 percentage points. This activity demonstrates that a context-based socialization approach grounded in adolescents' real digital experiences is more effective in building cyber security awareness than generic technical approaches, while contributing to shaping a generation that is not only digitally proficient but also digitally safe.